Geo-environmental parametric 3D models of SARS-CoV-2 virus circulation in hospital ventilation systems - Zorzi, Carla Gabriela Carlot (2021)
Adsorption is a unit operation widely used for the tertiary treatment of the most diverse effluents, whose mechanism is based on removing recalcitrant compounds from the organic and inorganic origin. In this process, choosing a suitable adsorbent is a fundamental point. This review article focuses on the adsorbents with natural geological origin: minerals, clays, geopolymers, and even wastes resulted from mining activity. Therefore, over 450 articles and research papers were explored. These materials' main sources are described, and their characteristics, composition, and intrinsic properties are related to adsorption. Herein, we discuss the effects of several process parameters, such as pH, temperature, pollutant, and adsorbent concentration. Furthermore, equilibrium, kinetics, and thermodynamic aspects are also addressed, and relevant regeneration prospects and final disposal. Finally, some suggestions and perspectives on applying these adsorbents in wastewater treatment are presented as future trends.